IMPROVING EFL STUDENTS’ WRITING THROUGH PEER TUTORING [MENINGKATKAN KETERAMPILAN MENULIS MAHASISWA PEMBELAJAR BAHASA INGGRIS SEBAGAI BAHASA ASING MELALUI TUTORING OLEH TEMAN SEBAYA] - Rentauli Mariah Silalahi (Polyglot: Jurnal Ilmiah)
This study investigates the writing challenges faced by Indonesian EFL students and examines the effectiveness of peer tutoring in enhancing their writing skills. Through a mixed-methods approach, data were collected via open- and closed-ended survey responses and writing assessments’ scores to 40 students as tutees, and semi-structured interviews with 4 peer tutors. The findings indicate that students struggle primarily with vocabulary, grammar, sentence structure, and translation. These difficulties are interconnected, as limited vocabulary and grammatical knowledge hinder their ability to construct clear and coherent sentences. The results show that most students found peer tutoring beneficial, as it provided a supportive learning environment, personalized guidance, and reduced the pressure of traditional teacher-student interactions. However, some students reported minimal or no improvement, which could be attributed to factors such as lack of engagement or scheduling conflicts. These findings are analyzed through the lens of Vygotsky’s Sociocultural Theory, particularly the concepts of the Zone of Proximal Development and scaffolding. The study highlights how peer tutoring facilitates learning by providing social interaction with more knowledgeable peers, enabling students to progress beyond their current level of competence. These insights suggest that educational institutions should integrate structured peer tutoring programs into EFL writing courses and provide teachers with the necessary training and resources to offer appropriate scaffolding tailored to students’ individual challenges. Future research should explore targeted interventions for students with lower engagement and investigate strategies to enhance the effectiveness of peer tutoring in EFL writing instruction.